INDUCED BIOSYNTHESIS OF α-AMYLASE BY GROWING CULTURES OF BACILLUS STEAROTHERMOPHILUS - Welker, N. E. (1963)
Welker, N. E. (Western Reserve University, Cleveland, Ohio), and L. Leon Campbell. Induced biosynthesis of α-amylase by growing cultures of Bacillus stearothermophilus. J. Bacteriol. 86:1196–1201. 1963.—The maximal differential rate (K) of α-amylase synthesis was usually two to three times that of the sucrose control culture, over an inducer concentration range of 5 × 10(−4) to 1 × 10(−3)m. With maltotetraose, higher concentrations decreased the K value, whereas higher concentrations of maltose were needed to obtain maximal K values. Glucose, in concentrations from 10(−5) to 10(−2)m, had no effect on the differential rate of enzyme synthesis. Cultures growing on maltotriose, maltotetraose, maltopentaose, and maltohexaose exhibited the same growth rate (k) and differential rate of α-amylase synthesis over a concentration range of 2.92 × 10(−4) to 1.46 × 10(−2)m. Growth of cultures in various concentrations of pure maltose revealed that with concentrations of maltose ranging from 2.92 × 10(−3) to 1.46 × 10(−2)m the K value for α-amylase production increased 18-fold. The amount of maltose utilized, during the growth period, at each concentration of maltose, was constant. Diauxic type growth was observed when maltose was used in addition to another carbon source (i.e., glucose, glycerol, fructose, or sucrose). Maltose was not utilized until the other carbon source had been metabolized. Phenyl-, methyl-, and ethyl-α-d-glucoside and methyl-β-d-maltoside were good inducers of α-amylase and would not serve as a carbon source in a chemically defined medium supplemented with 0.1% casein hydrolysate. These compounds were therefore gratuitous inducers of α-amylase. Isomaltose, panose, butyl-α-d-glucoside, and methyl-α-d-maltotetraoside were not effective as inducers of α-amylase. Fructose had an inhibitory effect on constitutive (41%) and inducible (55%) α-amylase formation; glucose had no effect.